On the performance of switching methods in space division multiplexing based optical networks - Sridhar Iyer (Computer Science and Information Technologies, 2020)
In the current work, for space division multiplexing based optical networks (SDM-b-OTNs), we investigate the performance of various switching methods with a variation in traffic evolution over different time frame periods. Initially, comparison of the existing methods viz., independent switching (InSw), frequency switching (FqSw), and space switching (SpSw) demonstrates that (i) over longer periods of time frame, FqSw provisions low network usage, and (ii) SpSw offers low network usage for shorter periods of time frame; however, as time frame increases to longer periods, SpSw starts to outperform InSw. Next, we investigate a hybrid switching (HySw) method which begins by implementing InSw and then shifts to the use of SpSw after the activation of specific numbers of space channels. The simulation results demonstrate that HySw provisions substantial savings on the costs incurred for switching, and with lower space channel values it also offers a balance in the trade-off which occurs between the costs associated for activating the space channels and that incurred for switching.